An executive guide to IFRS : content, costs and benefits to business - Walton, Peter J. (Chichester, West Sussex, UK : Wiley, 2011)
''A comprehensive and invaluable guide to IFRS which users will find indispensable in correctly applying the complex and onerous requirements of IFRS and IAS.' Steve Collings, FMAAT, FCCA, Leavitt Walmsley Associates and author of Interpretation and Application of International Standards on Auditing. International Financial Reporting Standards have been mandatory in the EU since 2005 and are rapidly being adopted by countries throughout the world. In this environment it is increasingly important for managers, executives and CEOs to understand the background of the IFRS and their main requirements. In An Executive Guide to IFRS: Content, Costs and Benefits to Business, Peter Walton provides a concise and accessible guide to the principal features of IFRS, explains why they are useful, looks at their impact on businesses, and provides some of the context to help define their global role. The book is divided into three sections. Part one deals with the convergence process and its costs and benefits, and gives background on the story so far. Part two contains the main technical content of the book and provides an analysis of the main issues under IFRS reporting, including: The content of financial statements, Investments in other companies, Income Statement and Balance Sheet items, IFRS for SMEs, and A comparison with US GAAP. Part three covers the creation of the IFRS, provides details of the IASB's standard-setting process, and describes how people outside the IASB can participate in the process and lobby effectively. It also examines the history of the IASB, and includes a chapter based on the author's observation of the standard setters in action. An Executive Guide to IFRS is an invaluable resource for anyone seeking to understand the essentials of International Financial Reporting Standards'--
'This book explains the movement towards a worldwide standard of financial reporting for listed companies as an aid to efficient investment'--
Includes bibliographical references (p. 217-220) and index.
Keywords: International financial reporting standards; Financial statements -- Standards; International business enterprises -- Accounting -- Standards